(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
Biometric images are detailed, unique, difficult to alter and durable over the life of an individual, making them suitable as long-term markers of human identity. In recent years cryptographic algorithms have been suggested to secure biometric images. In this paper, mainly consider on fingerprint images and we propose a new algorithm to encrypt and decrypt fingerprint images by using a specially designed Elliptic Curve Cryptography (ECC) procedure. In addition, to increase the confuseing effect of fingerprint encryption, we also utilize Arnold Cat Map (ACM) for a shuffling of pixel locations in our method. Moreover, we use block ciphers for reducing the computational space and time. Experimental results are carried out with detailed analysis to demonstrate that the proposed encryption-decryption algorithm is advantageous in several different aspects including efficiency, security and flexibility.